One Hundred Years of Data in the Journal of Turkology - Uzun, Cemile (Istanbul Universitesi, 2025)
This study aims to examine the articles published in the Journal of Turkology between 1925 and 2024 through a data-centered perspective and to reveal the transformation of the concept of data and the types of data used in the field of Turkology over time. Based on the view that data is not merely content but a fundamental component of academic knowledge production, the articles in the journal were analyzed across three historical periods: 1925–1950, 1950–2000, and 2000–2024. The tripartite classification highlights the changing approaches to data in Türkiyat Mecmuası. Each period was evaluated in terms of the nature of the relationship established with the data. The study conducted a comparative analysis of data types, data collection methods, the relationship between data and meaning, and analytical approaches used in each era. In the post-2000 period, with the influence of digitization, data diversified both qualitatively and quantitatively; digital resources, language technologies, and visualization techniques came to the forefront. The findings reveal that the Journal of Turkology not only reflects the thematic trends of Turkological research but also serves as a historical record of how the Turkish academic world has conceptualized and interacted with data. © 2025. Uzun, C.
Türkiyat Mecmuası’nda Verinin Asırlık Serüveni
Keywords: Academic Transformation; Akademik Dönüşüm; Data-Driven Analysis; Disiplinlerarası Yaklaşım; Interdisciplinary Approach; Journal of Turkology; Turkology; Türkiyat Mecmuası; Türkoloji; Veri Tabanlı Analiz